Recording of Three Monogenean Parasites of the genus Gyrodactylus for the first time from fishes of Diyala River, Iraq (Journal of the College of Basic Education, 2022)
First record in Iraq Three Monogenean species of the genus Gyrodactylus from Diyala River, Diyala province. The description, measurements and illustrations of these parasites were given.Keywords: Monogenean, Parasites, Fishes,Diyala River, Iraq